Posterior superior internal impingement: an evidence-based review. Issue 5 (6th April 2010) - Castagna, Alessandro; Garofalo, Raffaele; Cesari, Eugenio; Markopoulos, Nikolaos; Borroni, Mario; Conti, Marco
Abstract : Over the last decade, the concept of internal impingement has continued to evolve, and the frequency with which this condition is recognised continues to increase. This syndrome should be clearly differentiated from the classical (external) impingement that is thought to be caused by compression of the subacromial bursa, long head of the biceps tendon and rotator cuff (RC) by the coraco-acromial arch. Internal (posterosuperior) impingement syndrome is typified by a painful shoulder due to impingement of the soft tissue, including the RC, joint capsule and the posterosuperior part of the glenoid. The aetiology of this syndrome is unclear, but hypotheses include anterior shoulder instability or micro-instability, contracture of the posterior capsule, reduced humeral retroversion and scapular dyskinesis. Non-operative therapy represents the first line of treatment for this syndrome and includes the management of pain, stretching of the posterior capsule and a muscle strengthening programme. Surgical treatment should only be considered when conservative management fails. A number of different surgical procedures have been proposed, but the results are variable. The success rate is generally improved when the subtle instability, associated with internal impingement, is also addressed.